Measuring stability in Islamic rural banks: The influence of bank concentration and capital - Desti Indah Pratiwi; Adennia Oktaviana Fadli; Arum Setyowati (Sebelas Maret Business Review, 2023)
The Islamic Rural Bank, commonly referred to as BPRS in Indonesia, is a vital player in the country's economic landscape, providing limited banking services rooted in Islamic principles. BPRS serves as an economic catalyst across various regions, including both urban and rural areas, thereby shaping the level of concentration, capital ownership, and stability in the financial sector. This study centers its focus on BPRS, a unique financial institution that contributes significantly to the nation's economy. The research, conducted throughout Indonesia in 2020 from the first to the fourth quarter, offers fresh insights into BPRS as a subject of study. By employing quantitative methods, the study endeavors to explore the impact of concentration and capital ownership on the stability of BPRS in Indonesia. Interestingly, the findings in this research suggest that concentration levels don't provide a clear explanation of the relationship between BPRS concentration and stability. On the other hand, BPRS capital ownership is positively and significantly related to stability, indicating that a strong capital base enhances the overall stability of these Islamic rural banks. These results offer valuable insights into the financial dynamics of BPRS in Indonesia, providing essential information for policymakers and stakeholders as BPRS continues to drive the nation's economic development.